Risk assessment for type 2 diabetes mellitus in Muttanallur village, Bangalore, India - Dasaraju, Suma; D., Sudeepa; Barik, Debasish; Hiremath, Lalitha D. (International Journal of Research in Medical Sciences, 2019)
Background: Diabetes is a major cause of morbidity and mortality worldwide. There are certain risk factors involved in the development of type 2 DM. Affordable, quick and easily available validated tools are required for assessment of risk factors for type 2 DM. Using one such questionnaire, Finnish Diabetes Risk Score [FINDRISK], we have conducted an observational study in a rural area to identify and assess the risks for the development of type 2 DM. Methods: This cross sectional, observational, community-based study was undertaken, in Muttanallur Village, Bangalore. After the application of inclusion and exclusion criteria, 487 subjects were included. According to the final score obtained with the FINDRISK questionnaire, the individuals were classified into mild, moderate, high and very high-risk groups. Results: After the analysis of the variables, 253 individuals (52%) came under moderate risk with a score of (7-14) and 6 (1.2%) were categorized as having very high risk. Females, subjects above the age group of 45 years, having BMI ≥30 kg/m2, waist circumference of ≥37 inches, not having 30 minutes of daily physical activity and consumption of vegetables and fruits, with history of hypertension, high blood glucose during pregnancy or in the past, were having higher moderate to high risk prevalence and had more chances of developing type 2 DM (p value <0.001). Conclusions: As per the results of this study authors concluded that there was a statistically significant association between certain clinical variables with the development of future type 2 DM.